Moral Values in "Alya: The Daughter of War" Movie (2017) Directed by Can Ulkay: A Content Analysis Study - Febri Aini Adalta; Ira Maisarah (Journal of English for Specific Purposes in Indonesia, 2024)
Film is a kind of social communication that can be made base on the social reality that exists in and around the setting in which it is set. This study aims to examine the moral values in the movie Ayla: The Daughter of War. The content analysis method was employed in this study. Primary and secondary data are the two categories of data used in this study. The key information gleaned straight from the movie Ayla the Daughter of War is known as primary data. secondary data included documents, journals, and other sources of information that could help with the study. This study employs two methods to collect data: documentation procedures and observation approaches. This study used Roland Barthes' semiotic analysis to gain a more precise understanding of the symbols and significance of the ethical lesson conveyed in the movie Ayla: The Daughter of War. The finding showed that there are eight moral values—humanity, helping each other, tolerance, brave, responsible, love and affection, human connections to God, and keeping promises—were identified by researchers in this movie. It can be concluded that there are numerous moral lessons and prerequisites for the meaning of the film. This movie shows that despite differences in racial, cultural, and religious backgrounds, empathy, love, and compassion can still exist. Aside from that, this movie also teaches that love and affection can arise from an honest heart regardless of a person's biological link to another person.